Memory impairments and increased GFAP expression in hippocampal astrocytes following hypercaloric diet in rats - Eduardo Fernandes Bondan; Carolina Vieira Cardoso; Maria de Fátima Monteiro Martins; Rosemari Otton (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: Hypothalamic inflammation and glial fibrillary acidic protein (GFAP) overexpression in astrocytes are well described in obese animals, as are some cognitive and memory deficits. As the hippocampus plays important roles in the consolidation of information, this investigation aimed to observe the memory function and the astrocyte expression of GFAP in the hippocampus of rats that received either a hypercaloric or a normocaloric diet. Methods: Adult male Wistar rats received a high-fat (cafeteria) or a standard diet for 60 days. On the 61st day, the rats were submitted to the novel object recognition (NOR) test at three and 24 hours after the first contact with objects, to assess short-term and long-term memory, respectively. Thereafter, the rats were euthanized and their brains were collected for GFAP immunohistochemical investigation in the hippocampus (CA1, CA2, CA3 areas) and hypothalamus (periventricular and arcuate nuclei). Astrocytic reactivity was assessed by morphometry. Different white adipose tissue depots and brown adipose tissue were weighed to calculate the adiposity index. Results: The hypercaloric diet increased body weight gain, adiposity index, white adipose tissue weight (epididymal, subcutaneous and retroperitoneal) and brown adipose tissue weight. Rats fed with the hypercaloric diet showed short-term and long-term memory impairments in the NOR test, as well as increased GFAP expression in astrocytes from all analyzed hypothalamic and hippocampal areas. Conclusion: This astrogliosis suggests that the neuroinflammatory response also occurs in the hippocampus and may be involved in the memory losses observed in obese/overweight animals.